Analisi Pengaruh Aplikasi Tiktok (Tiktok Shop) Terhadap Kepuasan Konsumen dalam Pembelian Online Melalui Promosi Influencer - Fatio D Situmorang; Reyka Triana Yohana Sidabutar; Tasya Novi Ardana (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2025)
This study explores how influencer promotions affect consumer satisfaction levels in shopping through TikTok Shop. Using a descriptive qualitative method, this study collected data through interviews and user review analysis to understand the factors that contribute to customer satisfaction. The results revealed that aspects such as influencer credibility, engagement in live shopping sessions, and transparency in product reviews play an important role in increasing buyer satisfaction. However, several challenges are still faced, such as product mismatch with description and inadequate customer service. These findings provide valuable insights for business actors and influencers in developing more effective marketing strategies to improve consumer shopping experiences.